ADAPTIVE CONTROL SYSTEM FOR DRYING PELLETS FOR SNACK PRODUCTION - SMOLII, OLEKSANDR; MYKYTYSHYN, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Drying of pellets is an important stage of production, as it ensures their quality, long-term storage and proper culinary properties. At the same time, the products can be produced in large quantities and stored without refrigeration. Nowadays, various types of dryers are used in the production of pellets, including convection, infrared, vacuum. As well as we have to achieving a certain level of moisture in the finished product, it is also important to ensure the quality of the product. After all, too fast or uneven drying can cause internal stresses in the dough, which can lead to the appears of cracks and increased brittleness. High temperatures or uneven drying can affect the protein structure and change the taste characteristics of the products. The theoretical definition of drying kinetics includes many interrelated processes. It has been studied that the drying process of pellets is similar to the drying process of pasta, and is well described by models created to describe the drying of pasta. Achieving quality indicators of the final product is possible only if drying is controlled and corrected throughout the entire technological process. Typically, control systems are built in such a way that drying modes are set based on predetermined conditions of the drying environment, namely the required air humidity and temperature in the drying process, and the air flow rate. These parameters are formed based on previous experience for each specific type of product. This approach can be called predictive temperature and humidity control. In this case, it is expected that the properties of the raw material remain unchanged from batch to batch, or that the discrepancy is within acceptable limits, which allows maintaining the same modes for different batches of products of the same type. However, even small changes in the structure or shape of the product can cause significant deviations in the drying rate. This article considers a control system for convection drying of pellets, in which the drying process is carried out along a predetermined trajectory of product humidity change. Due to the nonlinearity of the system and the long duration in time, ensuring the required trajectory requires not only a response to changes, but also a forecast of the process depending on the change in parameters. Such a forecast can be made on the basis of a mathematical model. Model forecasting allows to adjust the drying parameters depending on the actual properties of the product. In order to provide feedback, real-time product weighing was used. Using forecasting based on a mathematical model and introducing additional feedback loops into the classical drying control system allowed automatically adjust the operating modes of the drying oven and ensure a given drying speed by adjusting the characteristics of the drying environment.